Facial bone reconstruction with prefabricated vascularized calvarium flaps in children and young adults: Advantages and long-term results. Issue 12 (December 2016) - Rüegg, Eva Meia; Gniadek, Paul; Modarressi, Ali; Baratti-Mayer, Denise; Pittet-Cuénod, Brigitte
Abstract: Introduction: Reconstruction of facial bone defects in children is challenging. The use of well-vascularized bone is mandatory to obtain stable lasting results. This study reports our experience of facial bone reconstruction using prefabricated vascularized calvarium flaps. Methods: Retrospective case series of 50 patients who underwent 52 maxillary, malar, and mandibular reconstructions between 1988 and 2014 using prefabricated vascularized calvarium flaps. Forty-nine patients suffered from noma sequels; one patient had craniofacial cleft Tessier 3–11. Surgery consisted of a two-step procedure beginning with flap delay and prelamination with skin grafting on the galea. Flap harvest followed at least 2 weeks later (range, 2–16 weeks), including a full-thickness calvarium fragment, which was set into the facial defect. Results: Early complications concerned wound healing and infections requiring surgical revision in six patients at the recipient and six at the donor site. There was one flap loss. Clinical long-term assessment at 15-year median follow-up (range, 1–27 years) showed good results, assuring facial height and contour. Radiological long-term results demonstrated excellent integration of the flap to the adjacent facial skeleton of the growing child. Conclusions: Prefabricated vascularized calvarium flaps are an effective, safe and lasting method for reconstruction of facial bone defects in children.